Seasonal flood risk for paddy rice production in northwest Peninsular Malaysia - Mohamed Rehan, Balqis; Bweya, Alice Zimba; Mok, Yi Wen; Zulkafli, Zed; Raffar, Nurfarhana (Taylor and Francis, 2024)
Managing flood risk to crop productions can be made cost-effective by considering the seasonality of flood hazard. This study attempts to quantify expected seasonal flood risk to paddy production in northwest Peninsular Malaysia. The seasonal flood risk was quantified following the region’s standard planting seasons and accounts the seasonal annual maxima flood and potential losses to the crop production. The highest expected annual damage (EAD) is from the wet planting season between September and November during the vegetative and reproductive growth phases, amounting to more than MYR 700,000 EAD. These months coincide with the northeast monsoon season, typically occurring from November to March each year. Seasonal flood risk remains a threat to the nation, and the quantified expected losses provide strong justification of the need for a proactive and strategic action plan. © 2024 IAHS.